ANALISIS USAHA DAN REKOMENDASI STRATEGI PENGEMBANGAN TEFA - Sangadah, Hanik Atus; Aprilliani, Fenny; Riyadi, Cica Putri; Dwi Atmala, Refira (Fakultas Pertanian Universitas Janabadra, 2025)
Tefa (Teaching Factory) is a learning media developed to carry out production activities continuously.Tefa are developed by the Department of Agriculture to focus on Pineapple processing production activity such as Pineapple Pie which is currently existing. The necessary effort to continue maintaing Tefa's existence and productivity is to formulate a Tefa development strategy. The method used to formulate Tefa's development strategy recommendations is started from Tefa’s current business analysis by looking at the Internal-External (IE) matrix. Followed by analysing internal and external factors from all actors involved in the supply chain. After the IFE-EFE matrix is compiled and assessed by experts, then a SWOT analysis will be carried out to obtain a list of strategy recommendations. Finally the priority order of strategies is determined by QSPM analysis. The results of the supply chain activity analysis show that the highest added value will be obtained by Tefa if it uses flow 2, namely buying raw materials directly from farmers. While the result of the priority recommendations for the development strategy is Tefa actively begins to compile and implement the 4P marketing mix marketing strategy.